Analysis of Human Resource Management Challenges in Enchancing Employee Performance in The Retail Industry - Mohamad Jidan, Deva Falahian; Bakr Muhlison, Muhammad (Cita konsultindo, 2025)
The modern retail industry faces challenges in human resource (HR) management, such as high turnover, low motivation, and ineffective training programs, especially with the dominance of millennials and Gen Z, who demand more adaptive HR strategies. This study aims to identify the main challenges in HR management, their impact on employee performance, and applicable strategies. The method used was descriptive qualitative with in-depth interviews and observations. The results showed that the main problems include high turnover, low motivation due to unfair compensation and reward systems, inconsistent training, and communication gaps across generations. These findings emphasize the importance of retention strategies, transparent reward systems, needs-based training, and a collaborative work culture to improve employee loyalty and performance. This study has practical implications for HR management in the retail sector and enriches academic studies. Future studies are recommended to involve a wider range of respondents and incorporate quantitative methods for more representative results.